COVID-19 and the Accelerated Shift to Technology-Enabled Work from Home - Marcus, J. Scott; Petropoulos, Georgios; Aloisi, Antonio (IE University, 2022)
People have been working remotely from many locations for many years, but the growth in work from home has historically tended to be slow in both the USA and the EU. Most of those who worked from home did so for only a portion, often a small portion, of their working hours. COVID-19 has given a huge impetus to working from home for those jobs that can be performed from home. Work from home can be a driver of sustainability in the context of the green and digital transition. Data on productivity effects of this shift does not offer a compelling view on whether there have been gains or losses, given the multifaceted set of elements that need to be considered and contrasted. However, many workers appreciate and benefit from the flexibility that work from home provides. At the same time, this shift has significant implications for many aspects of our lives, and it raises a number of possible concerns that may need to be addressed by public policy. There is a risk that some groups (women, young workers and those who are less technically capable of using digital technology) may suffer from decline in wages and loss of opportunities for promotion and training. There are some indications of mental health issues due in part to the inability to separate work from private life, increased work hours, and the need to deal with children who are at home, but it is difficult to disentangle aspects that are caused by work from home in general from those that are primarily related to the pandemic. By adopting a comparative approach, this research note explores these aspects and the main differences between the USA and the EU. It concludes by highlighting the key implications for public policy in terms of work-life balance, gender gaps, skill acquisition, modernisation of workflows, technology adoption, managerial culture and flexibility enhancement.
Keywords: Work from Home;Digitalization;COVID-19;Labour Market;Labour Productivity; Work from Home; Digitalization; COVID-19; Labour Market; Labour Productivity; ODS 9 - Industria, innovación e infraestructura